2020
DOI: 10.21203/rs.3.rs-36044/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical Outcome of Meningitis and Its Risk Factors Among Children Admitted in Debre Markos Referral Hospital Pediatric Ward, Northwest Ethiopia,2019

Abstract: Background:Meningitis remains a major cause of mortality and morbidity in patients in many countries of the world including Ethiopia. This study aimed to assess clinical outcomes and associated risk factors of meningitis among children who were admitted to Debre Markos Referral Hospital from January 2017 to December 2018.A backward stepwise multivariable logistic regression was applied with 95% confidence interval of odds ratio (OR) andstatistical significance less than 0.05 p-value were taken as cut off value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Children appear sicker and in infants, the main presenting features are poor feeding, lethargy, seizures and paradoxical irritability. 12,13 Studies have shown that fluid management may be associated with decrease in neurological sequelae in children. 14 Hadi N et al15 did one study in Iran and in their study positive CSF cultures were more in children less than five years of age in 57.1% patients while inn our study about 60% of patients were aged less than five years.Sallam AKA16 study done in Yemen showed that the age group which presented with meningitis was between 4 months and 3 years.…”
Section: Discussionmentioning
confidence: 99%
“…Children appear sicker and in infants, the main presenting features are poor feeding, lethargy, seizures and paradoxical irritability. 12,13 Studies have shown that fluid management may be associated with decrease in neurological sequelae in children. 14 Hadi N et al15 did one study in Iran and in their study positive CSF cultures were more in children less than five years of age in 57.1% patients while inn our study about 60% of patients were aged less than five years.Sallam AKA16 study done in Yemen showed that the age group which presented with meningitis was between 4 months and 3 years.…”
Section: Discussionmentioning
confidence: 99%